2022
DOI: 10.1097/qmh.0000000000000344
|View full text |Cite
|
Sign up to set email alerts
|

Does Root Cause Analysis Improve Patient Safety? A Systematic Review at the Department of Veterans Affairs

Abstract: Background and Objectives: While root cause analysis (RCA) is used to analyze medical errors with a systems approach, evidence demonstrating its effectiveness in reducing patient harm remains sparse. The heterogeneity of the RCA methodology at different health care organizations has posed challenges to studying its value. The Department of Veterans Affairs (VA) has an established and standardized RCA approach, making it an ideal context to study RCA's impact. This review assessed whether implemented interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
7
2
Order By: Relevance
“…Given that performing ACAs could help clinicians identify potential causes or risk factors of PedVAEs, reporting and discussing these ACAs could lead to greater attention to the event and its prevention. Increased reporting in root cause analyses and ACAs have been associated with improved patient outcomes . In the present study, however, both reliable and nonreliable reporters of ACA data showed a centerline shift in PedVAE rates.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Given that performing ACAs could help clinicians identify potential causes or risk factors of PedVAEs, reporting and discussing these ACAs could lead to greater attention to the event and its prevention. Increased reporting in root cause analyses and ACAs have been associated with improved patient outcomes . In the present study, however, both reliable and nonreliable reporters of ACA data showed a centerline shift in PedVAE rates.…”
Section: Discussioncontrasting
confidence: 66%
“…Increased reporting in root cause analyses and ACAs have been associated with improved patient outcomes. [30][31][32] In the present study, however, both reliable and nonreliable reporters of ACA data showed a centerline shift in PedVAE rates. This shift may be associated with the PedVAE education that was provided to both the reliable and nonreliable reporters of ACA data.…”
Section: Limitationscontrasting
confidence: 50%
“…A review of the existing literature has identified no papers directly addressing the validity of RCA in adverse-event investigation in health or in psychiatry. Most authors have focused on the lack of evaluation of effectiveness of RCA in health, especially with reference to recommendations and action plans, 12,[17][18][19][20][21][22] which are the output of RCAs. Several authors have considered whether RCA is the best method to investigate adverse events in health.…”
Section: Use Of Rca In Healthmentioning
confidence: 99%
“…In “Does Root Cause Analysis Improve Patient Safety? A Systematic Review at the Department of Veterans Affairs,” Shah and colleagues1 examine if root cause analysis in the Veterans Health Administration has been effective. The article shows that some investigators collect data on the impact of the improvement, which is encouraging and reassuring.…”
Section: Lasting Improvement or Fleeting Successmentioning
confidence: 99%